Facilitating epistemic fluency of undergraduate students during the interdisciplinary research process - van Lambalgen, Rianne M.; de Vos, Febe (Frontiers in Education, 2023)
In this article we show how students share knowledge when integrating disciplinary insights in an interdisciplinary research project. More specifically, this research shows how students communicate to create a shared mental model during moderated sessions with use of CoNavigator as an interdisciplinary collaboration tool or Miro as an online mind map tool. The study focuses on the interdisciplinary capstone of the Liberal Arts and Sciences bachelor program at Utrecht University (LAS), where students collaborate in multidisciplinary groups by going through the interdisciplinary research process (IRP) as designed by Repko and Szostak (2020). This process asks students to define an interdisciplinary research question, to define disciplinary insights and combine each other’s disciplinary knowledge to create a more comprehensive understanding of their research question. In this research we moderated seven sessions with either CoNavigator or Miro and through observations of communication during the sessions we found that the tools help students to actively work with different ways of knowing and to define and connect disciplinary differences. We relate our findings to epistemic fluency and argue that LAS-students exhibit epistemic fluency when working with the tools, but also develop this throughout the session. It appears that the epistemic fluency students already possess prior to the IRP can be further developed by the epistemic fluency expressed by teammates during the tool session. This enables the group to work towards a shared epistemic fluency, in which they demonstrate a shared understanding of the value of the disciplinary contributions in creating understanding of the interdisciplinary research theme they are addressing.